Pengendalian Kualitas Produk Tempe menggunakan Metode Six Sigma di UMKM Tempe Ibu Ida Alisa - Muljoko Muljoko; Ayudyah Eka Apsari (Jurnal Rekayasa Proses dan Industri Terapan, 2025)
UMKM owned by Mrs. Ida Alisa use 150 kg of soybeans which produce around 400 pcs of tempeh per day. MSMEs owned by Mrs. Ida Alisa have 5 employees in the traditional tempeh production process with the tempeh production process covering several stages, namely soaking, peeling, boiling, adding yeast, packaging, and fermentation. Six Sigma is a structured and systematic problem-solving method using the DMAIC (define, measure, action, improve, control) standard as the process flow. The main focus of Six Sigma is on quality improvement to meet customer satisfaction. The number of defects in tempeh products is Gross with a total of 299 with a defect percentage of 39.2%, packaging with a number of 228 with a defective percentage of 29.9%, and Texture with a number of 236 with a defect percentage of 30.9%. From this percentage, the highest percentage value can be obtained, namely on dirty tempeh defects. From the results of data processing, suggestions for improvement were obtained, among others, training and socialization to operators in order to maximize the production process, giving directions to operators and maintenance to check before starting production so that the readiness of the machine to be used can be tested. In addition, a Standard operating procedure (SOP) was made regarding sorting and soaking processes for the production process.